Experimental Study of Roughness Analysis of AISI 316L Material using Fiber and CO2 LBM - Tukaram Sargar; Aniket Jadhav; Nitish Kumar Gautam (International Journal of Solid State Innovations & Research, 2024)
Laser beam machines have gained significant attention as a precise and versatile method for cutting and shaping materials in various industries. This study investigates the surface roughness characteristics of SS 316L, a commonly used stainless steel, when subjected to laser beam machining using both fiber and CO2 laser sources. The aim of this research is to compare the effects of these two laser types on the final surface finish of SS 316L. The experiments were conducted by varying laser processing parameters such as laser power, cutting speed, and assisting gas pressure to optimize the machining conditions for each laser type. Surface roughness measurements are performed using a surface profilometer, and the obtained data is statistically analyzed to assess the influence of the selected parameters on surface quality. The results show that the CO2 laser machining process generally produces smoother surface finishes compared to fiber laser machining for SS 316L material. The findings provide valuable insights for selecting the appropriate laser source and machining parameters to achieve desired surface roughness in SS 316L material processing. This research contributes to a deeper understanding of the interaction between laser beam sources and material properties, aiding in the optimization of laser machining processes for improved surface finish in stainless steel applications.
Keywords: ANOVA; CO2 laser; DOE; Fiber laser; Optimisation; Surface roughness